Mindfulness in Higher Education: Comparative Analysis in Students of Psychology and Food Engineering - Quimi Lucin, Emily Michelle (2025)
The research carried out at the Technical University of Machala compared the levels of mindfulness between students of Clinical Psychology and Food Engineering, using the Mindful Attention Awareness Scale (MAAS). The sample consisted of 299 students, 156 from Clinical Psychology and 143 from Food Engineering. In the comparative analysis, the Mann-Whitney U test and the effect size were used, with Rosenthal's r coefficient. A Simple Correspondence Analysis (CA) was also performed to explore the associations between MAAS items and mindfulness levels in each group. The results showed that Clinical Psychology students had significantly higher levels of mindfulness (M = 3.87) compared to those in Food Engineering (M = 3.53). This is attributed to training in mental health and psychological well-being in Clinical Psychology. The AC revealed that Clinical Psychology students had strengths in everyday tasks, but difficulties in maintaining attention in the present, while Food Engineering students showed problems staying in the present and a tendency to worry about the past. These findings suggest the need to integrate mindfulness programs into technical career curricula to improve psychological well-being and academic performance.